Tourism Informatics : Visual Travel Recommender Systems, Social Communities and User Interface Design / Nalin Sharda - Sharda, Nalin
"This book presents innovative research being conducted into Travel Recommender Systems, travel related on-line communities, and their user interface design"--Provided by publisher.